Consequences of convergence: Western firm's FDI activities in Central and Eastern Europe at the dawning of EU-enlargement - Stefan Eckert; Frank Rossmeissl (Journal for East European Management Studies, 2005)
Comparing all kinds of market entry, foreign direct investment (FDI) appears to be the most appropriate mode of foreign market. So called Market seeking FDI can be differentiated into those activities primarily aiming to realise psychic market proximity and into those activities mainly undertaken to realise physical market proximity. This differentiation is crucial because the number of FDI activities primarily done for reasons of psychic market proximity could decrease due to changes taking place in the CEE as well as an increasing cultural homogeneity. These tendencies give (a) MNEs already operating in CEECs for reasons of psychic market proximity potentials to restructure their current activities in the region and (b) MNEs striving to establish market presence in CEECs the possibility to consider modes of foreign market entry, which are less capital intensive than FDI like exporting. – – Wenn man alle Markteintrittsformen vergleicht, erscheinen FDI als die beste Art des ausländischen Markteintrittes. Sogenannte marktsuchende FDI können unterteilt werden in jene, die eine psychische Marktnähe anstreben und solche, die eine physische Marktnähe realisieren wollen. Diese Unterscheidung ist wichtig, da die Zahl der FDI-Aktivitäten, die auf eine psychische Nähe zielen, abnimmt und es zu einer zunehmenden kulturellen Homogenität in MOELändern kommt. Diese Tendenzen geben a) MNUs, die schon in MOELändern sind, aus Gründen der psychischen Marktnähe, die Möglichkeit, ihre Aktivitäten umzustrukturien und b) MNUs, die einen Markteintritt beabsichtigen, andere Formen anzuwenden, die weniger kapitalintensiv als Fdi sind wie der Export.
Keywords: 650; EU accession; Central and Eastern Europe; cultural convergence; foreign direct investment; subsidiaries of MNEs; foreign market entry mode